Development of intraspecific size variation in black coucals, white‐browed coucals and ruffs from hatching to fledging. (1st September 2020) - Giraldo‐Deck, Lina M.; Goymann, Wolfgang; Safari, Ignas; Dawson, Deborah A.; Stocks, Michael; Burke, Terry; Lank, David B.; Küpper, Clemens
Abstract : Most studies on sexual size dimorphism address proximate and functional questions related to adults, but sexual size dimorphism usually develops during ontogeny and developmental trajectories of sexual size dimorphism are poorly understood. We studied three bird species with variation in adult sexual size dimorphism: black coucals (females 69% heavier than males), white‐browed coucals (females 13% heavier than males) and ruffs (males 70% heavier than females). Using a flexible Bayesian generalized additive model framework (GAMM), we examined when and how sexual size dimorphism developed in body mass, tarsus length and bill length from hatching until fledging. In ruffs, we additionally examined the development of intrasexual size variation among three morphs (Independents, Satellites and Faeders), which creates another level of variation in adult size of males and females. We found that 27–100% of the adult inter‐ and intrasexual size variation developed until fledging although none of the species completed growth during the observational period. In general, the larger sex/morph grew more quickly and reached its maximal absolute growth rate later than the smaller sex/morph. However, when the daily increase in body mass was modelled as a proportion, growth patterns were synchronized between and within sexes. Growth broadly followed sigmoidal asymptotic models, however only with the flexible GAMM approach, residual distributions were homogeneous over the entire observation periods. These results provide a platform for future studies to relate variation in growth to selective pressures and proximate mechanisms in these three species, and they highlight the advantage of using a flexible model approach for examining growth variation during ontogeny.